Usulan Penerapan Otomatisasi Waktu OFF pada Killing Tank System Mode Steam Menggunakan Timer Omron H3CR-A8 di PT. Kalbio Global Medika - Muhammad Luthfan Maulana; Ibrahim ,; Reni Rahmadewi (Jurnal Ilmiah Wahana Pendidikan, 2023)
PT. Kalbio Global Medika (KGM) is one of the first and pioneer biopharmaceuticals in Indonesia and is a subsidiary of PT Kalbe Farma, Tbk., a leading healthcare provider in Indonesia and Southeast Asia. Liquid pharmaceutical waste from the results of drug production activities will be collected and processed in the Killing Tank System machine before being sent to Lippo's wastewater treatment plant so that the hazardous substances contained do not have a negative impact on the environment. There are 2 methods to kill bacteria in production waste water, namely by the method of ozonation and heating with steam. Currently, when the Killing Tank is in Steam mode, someone has to wait for 2 hours during the Holding process. When it's finished, the steam mode wastewater treatment process must be turned OFF manually by rotating the selector switch to stop the supply of steam from the boiler to the Killing Tank. If the process continues for more than 2 hours, there will be a waste of steam used during the wastewater treatment process. This research aims to provide a solution to this problem, namely to simplify and increase the effectiveness of the Killing Tank machine. By adding the Omron H3CR-A8 timer to the Killing Tank, it will automatically stop the steam supply from the boiler according to the set time.